Instrumented assessment of shoulder function: A study of inertial sensor based methods. (February 2020) - Bavan, Luckshman; Wood, Jonathan; Surmacz, Karl; Beard, David; Rees, Jonathan
Abstract: Background: Inertial sensors have the potential to provide objective and practical methods to assess joint and limb function in the clinical setting. The aim of this study is to evaluate the psychometric properties of inertial sensor metrics in the assessment of patients with subacromial shoulder pain. Methods: 25 patients with unilateral subacromial shoulder pain and 50 control subjects were recruited. Assessments were carried out on both shoulders for all participants during a short movement procedure. Patients had assessments repeated after receiving three months of physiotherapy. Inertial metrics evaluated included a smoothness measure and speed and power scores derived from the range of angular velocity and acceleration profiles. Individual shoulder scores and asymmetry scores were both evaluated in terms of reliability, known-group validity, convergent validity and responsiveness. Findings: Regression analysis identified age to be a significant predictor for all scores, therefore an age matched sub-cohort of control subjects was used for comparative analyses. All scores demonstrated inter-rater reliability (ICC = 0.48–0.82), were able to differentiate pathological from healthy shoulders (AUC = 0.62–0.91) and displayed significant changes following treatment. Scores derived from the range of acceleration and velocity profiles demonstrated the largest effect sizes (Cohens d = 0.8–1.35), and displayed the highest correlation with the Oxford Shoulder Score ( r = −0.40 – -0.58). Interpretation: The scores investigated demonstrate good psychometric properties and have potential to complement existing methods of assessment in the clinical or research setting. Further work is required to fully understand their clinical relevance and optimise assessment methods and interpretation.